Memikirkan Ulang Fondasi Definitif Filosofis dari Fotografi - Doweng Bolo, Andreas; Simanjuntak, Mardohar Batu Bornok (Sapientia Humana: Jurnal Sosial Humaniora, 2024)
This text discusses the problematic nature of photography since its inception. This disposition arises because photography is a manifestation of the dualistic thinking pattern matured by René Descartes and radicalized by Immanuel Kant. Photography, which began in the 19th century, was analog and relied on the permanent traces of time caused by chemical reactions. The strong claim of photography against the singularity of artistic work positions it as a threat to the value of art on one hand, while on the other, photography opens up various new approaches to artistic expression. Around 150 years after its birth, photography faced a serious challenge: even with digital technology, which eliminates the permanence of time traces, photography was considered "dead." This perceived death of photography led to ideological approaches viewing the existence of photography as post-medium discourse. By examining the development of major literature during the transition from analog to digital photography, this ideological approach further guides the discourse on photography as a metatheoretical and paradigmatic area. By shedding temporal elements, the discourse on photography moves more agilely within the framework of complex material monism—becoming a way of existing in a non-dualistic knowledge structure.